‘Get to know me, not the inmate’: women’s management of the stigma of criminal records - Grace, Anita (The British journal of criminology, 2022)
Criminologists have explored the experience of re-entry and the identified employment as productive of prosocial, post-carceral identities. They have also recognized that the stigma of a criminal record creates barriers to employment, and former prisons must find ways to manage this stigma if they are to be successful in the labour market. Yet existing studies on stigma management in the context of post-carceral employment have not addressed women’s unique needs and strategies. The current study uses interviews with 21 formerly incarcerated women to assess their accounts of how the stigma of criminalization can be managed with potential employers. Results highlight the utility of considering and supporting the role of employment in women’s post-carceral identities.